Pengaruh Kompetensi, Gaya Mengajar dan Motivasi terhadap Prestasi Mahasiswa - Gatot Kusjono; Suprianto Suprianto (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
This study aims to determine the effect of competence, teaching style and motivation on student achievement at Pamulang University. The study population was 247 respondents in the regular C odd semester 2019/2020 students in statistics and economics courses, while the research sample was 72 respondents using the Slovin formula. The research method used is descriptive qualitative with data analysis including: instrument test (validity and reliability), classical assumption test, multiple linear regression, F test, t test and coefficient of determination test. The research results obtained: 1) Competence partially does not affect student achievement; 2) Teaching style and motivation partially influence student achievement; 3) Simultaneously competence, teaching style and motivation have a significant effect on student achievement. These results are in accordance with the results of the F test, the value of Fcount (3.238)> of Ftable (2.740) with a significance of 0.027 less than 0.05.